Implementation of the Campus Teaching Program Batch 4 at SDN 155686 Untemungkur II - Sahlan Tampubolon; Suhendra Simamora (Journal on Education, 2023)
The primary purpose of the Campus Teaching program is to give students the opportunity to learn and develop through activity outside the lecture class, to help schools to provide educational services, optimized for all learners at the Primary School level in limited and critical conditions during the pandemic and give all students the opportunity to do so during the Primary School. As for the specific purpose of the Campus Teaching Program batch 4 2022 is the design program we are offering to state SDN 155686 Untemungkur II, I can present to the department of independent college, Students have contributed significantly to evidence that students have also become concerned and have played an active role in achieving a foreign ministry program for the advancement of national education and making Indonesian students trained to serve primarily in the field of education, through this program and students from all free courses to serve, contribute and collaborate with teachers creatively and innovative to advance literacy, Numeration and technology at state SDN 155686 Untemungkur II. As for the activities that are carried out during state SDN 155686 Untemungkur II are teaching activities, assisting technology adaptation, and assisting school and teacher administration.